Analisis dan Perancangan UI/UX dengan Metode User Centered Design pada Website DLU Ferry - Cavanaugh, Alif Bimananda; Rahmawati, Endra; Putra, I Gusti Ngurah Alit Widana (Jurnal Sistem Informasi Universitas Dinamika, 2021)
In order to achieve the company's business objectives, namely the distribution of sea transportation between islands throughout Indonesia and contribute economically and socially to the country and include the wider community with middle to lower economic class. PT Dharma Lautan Utama provides the DLU Ferry website with the address tiket.dlu.co.id. Based on the results of interviews with the IT/EDP Division and supported by the results of questionnaires based on the System Usability Scale (SUS) method for customers, it is known that the DLU Ferry website has a